2004
DOI: 10.1002/ijc.20418
|View full text |Cite
|
Sign up to set email alerts
|

Unconjugated bilirubin induces apoptosis in colon cancer cells by triggering mitochondrial depolarization

Abstract: Bilirubin is the principal end product of heme degradation. Prompted by epidemiologic analyses demonstrating an inverse correlation between serum bilirubin levels and cancer mortality, we examined the effect(s) of bilirubin on the growth and survival of colon adenocarcinoma cells. Adenocarcinoma cell monolayers were treated with bilirubin over a range of bilirubin:BSA molar ratios (0 -0.6), and viability was assessed colorimetrically. Apoptosis was characterized by TUNEL assay, annexin V staining and caspase-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 97 publications
2
88
1
1
Order By: Relevance
“…Previous studies suggested that UCB may inhibit cell growth and induce apoptosis in cancer cells (28,29). However, our results suggested that 20 mmol/L UCB does not significantly affect the growth and apoptosis of NPC cells both in vitro and in vivo (Supplementary Fig.…”
Section: Ucb Impairs the Invasion Abilities Of Npc Cellscontrasting
confidence: 56%
See 2 more Smart Citations
“…Previous studies suggested that UCB may inhibit cell growth and induce apoptosis in cancer cells (28,29). However, our results suggested that 20 mmol/L UCB does not significantly affect the growth and apoptosis of NPC cells both in vitro and in vivo (Supplementary Fig.…”
Section: Ucb Impairs the Invasion Abilities Of Npc Cellscontrasting
confidence: 56%
“…A small number of studies have suggested that UCB may inhibit proliferation and induce apoptosis in cancer cells (28,29). However, we did not observe an effect on NPC cells until the concentration of UCB reached 100 mmol/L (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Previous studies have shown that caspase-8 activity was significantly induced by BR treatment in Hepa 1c1c7 and rat neurons, suggesting BR-induced apoptosis is mediated by the extrinsic apoptosis pathway (Seubert et al, 2002;Vaz et al, 2011). However, caspase-8 induction appears to be cell-type specific, hence it remains unclear whether BR acts as a ligand for the death receptor or whether caspase-8 activity is increased indirectly by BR via oxidative stress in cellular organelles (Keshavan et al, 2004).…”
Section: Cyp2a5 Overexpressing Microsomes Have Increased Br Degradatimentioning
confidence: 99%
“…Fas) may be involved (Seubert et al, 2002;Vaz et al, 2011). However, BR-induced apoptosis via extrinsic pathway remains to be confirmed as the induction may be cell type-specific (Keshavan et al, 2004). BRinduced mitochondrial apoptotic pathway is also the result of production of lipid peroxides, hydrogen peroxide, and hydroxyl radical, as well as a decrease in glutathione content and reduction of the mitochondrial membrane (Kumar et al, 2008;Brites and Brito, 2012).…”
Section: Bilirubin Toxicitymentioning
confidence: 99%